The value of lung ultrasound score in neonatal respiratory distress syndrome: a prospective diagnostic cohort study - Huang, Chunyan; Zhang, Shaoqin; Ha, Xiaoming; Cui, Yanfang; Zhang, Hongxia (Frontiers in Medicine, 2024)
The accurate diagnosis of critically ill patients with respiratory failure can be achieved through lung ultrasound (LUS) score. Considering its characteristics, it is speculated that this technique might also be useful for patients with neonatal respiratory distress syndrome (NRDS). Objectives: The study was conducted as a prospective double-blind randomized study.Bivariate correlation analysis was conducted to investigate the relationship between LUS score and Oxygenation Index (OI), Respiratory Index (RI), and Sequential Organ Failure Assessment (SOFA) score. Spearman's correlation coefficient was used to generate correlation heat maps, elucidating the associations between LUS and respective parameters in different cohorts. Receiver Operating Characteristic (ROC) curves were employed to calculate the predictive values, sensitivity, and specificity of different scores in determining the severity of NRDS.Results: This study ultimately included 134 patients admitted to the intensive care unit (ICU) between December 2020 and June 2022. Among these patients, 72 were included in the NRDS cohort, while 62 were included in the Non-NRDS (N-NRDS) cohort.There were significant differences in the mean LUS scores between NRDS and N-NRDS patients (P < 0.01). The LUS score was significantly negatively correlated with the OI (P < 0.01), while it was significantly positively correlated with the RI and SOFA scores (P < 0.01). The correlation heatmap revealed the highest positive correlation coefficient between LUS and RI (0.82), while the highest negative correlation coefficient was observed between LUS and OI (-0.8). ROC curves for different scores demonstrated that LUS score had the highest area under the curve (0.91, 95% CI: 0.84-0.98) in predicting the severity of patients' conditions. The combination of LUS and other scores can more accurately predict the severity of NRDS patients, with the highest AUC value of 0.93, significantly higher than using a single indicator alone (P<0.01).Conclusions: Our double-blind randomized cohort study demonstrates that LUS, RI, OI, and SOFA scores can effectively monitor the lung ventilation and function in NRDS.Moreover, these parameters and their combination have significant predictive value in evaluating the severity and prognosis of NRDS patients. Therefore, these results provide crucial insights for future research endeavors.